Design and Synthesis of Terpyridine Functionalised Supramolecular Architectures - Delente, Jason Marcel (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Coordination-driven supramolecular assembly is an extremely useful tool to generate architectures of increased complexity and functionality, such as metallo-supramolecular gels and emissive materials. Interest in the terpyridine motif to realise such aims has continuously grown through the years due to its capacity to act as a key structural unit in the design of metallo-organic structures by binding strongly to many different metal ions. This thesis, entitled ?Design and Synthesis of Terpyridine Functionalised Supramolecular Architectures? describes the synthesis and characterisation of different building blocks adorned with the 2,2′:6,2′′-terpyridine (TPy) motif, and their uses to form d- and f-metal complexes and higher order self-assembled structures. Chapter 1 introduces the principles of supramolecular chemistry, with a particular focus on the use of 2,2′:6,2′′-terpyridines and 1,8-naphthalimides, and their uses in the formation of complexes and naphthalimide Tröger’s bases. The unusual shape of Tröger’s bases, and the properties that arise from this structure, are discussed, followed by several examples of lanthanides complexes featuring these motifs. A short review summarises the effects of the size of the lanthanide radii on the stability constants of the subsequent complexes. Recent examples of self-assembly of benzene-1,3,5-tricarboxamide scaffolds (BTA) are discussed with a focus on the formation of soft materials. The chapter is concluded by highlighting the research explored in the following chapters. Chapter 2 describes the functionalisation of the naphthalimide moiety through the imide using 4′-(4-aminophenyl)-2,2′:6′,2′′-terpyridine. The coordination of this ligand to various d-metal ions is described including the full characterisation of the resulting complexes. A brief comparison of the spectroscopic properties of the ligand and its corresponding Zn(II), Co(II), Fe(II) and Cd(II) complexes is discussed followed by a description of their electrochemical properties. Chapter 3 discusses the use of the aforementioned 4′-(4-aminophenyl)-2,2′:6′,2′′-terpyridine adorned 4-amino-1,8-naphthalimide to synthesise the corresponding 4-amino-1,8-naphthalimide Tröger’s (TBNap-TPy), and its full characterisation. The spectroscopic properties of TBNap-Tpy are discussed along with its aggregation-induced emission (AIE) properties. The use of TBNap-TPy as a fluorescent sensor for various nitroaromatics is described, and the capacity of TBNap-TPy to discriminate phenolic and non-phenolic nitroaromatics is demonstrated, including a detailed analysis of the interactions between TBNap-TPy and picric acid using UV-Vis absorption, emission, and IR spectroscopy, as well as DFT calculations, are described along with the effects of the presence of various anions. In addition, the limit of detection of picric acid and the effect of pH on the detection of picric acid are discussed. The synthesis and characterisation of a covalent organic polymer containing the TBNap moiety are described along with a detailed study of its use as a sensor for picric acid. This polymer is compared to the AIE active TBNapTPy. The synthesis of coordination polymers using Zn(BF4)2, Fe(BF4)2 and Co(BF4)2, and their characterisation, is discussed followed by their morphology studies. Finally, the spectroscopic and electrochemical properties of the ligand and the corresponding polymers are described. Chapter 4 focuses on the synthesis and uses of 1,3,5-benzene tricarboxamide functionalised with terpyridine (BTA-TPy) to generate supramolecular architectures able to form soft materials. A solution study of BTA-TPy in the presence of various Ln(III) ions (Ln = La, Sm, Eu, Gd, Tb, Yb and Lu) using UV-vis absorption and emission titrations is described, with an emphasis on the effect of the lanthanide contraction on the binding constants, determined through non-linear regression analysis. The formation of gels using BTA-TPy, and their modification using the aforementioned Ln(III) ions is described, focusing on the effects on their physical properties through morphological and rheological studies. The modification of the gel by diffusion of a ruthenium complex is also discussed in this chapter. Chapter 5 describes the design and synthesis, through several approaches, of a novel 1,3,5-benzene tricarboxamide functionalised with terpyridine using chiral amino-acids as spacer groups. While the desired tripodal molecule could not be obtained, the procedure for the formation of the TFA salt of L-Alanine-4’-(4-aminophenyl)-2,2':6',2''-terpyridine is described, along with its full characterisation, setting a platform for the functionalisation of 4′-(4-aminophenyl)-2,2′:6′,2′′--terpyridine with various amino acids. The conclusions are presented in Chapter 6, while Chapter 7 outlines the experimental details of the work presented herein. This is followed by literature references and appendices to support the preceding chapters.
APPROVED
Keywords: Terpyridine; Supramolecular chemistry; Tr?ger's base; 1,3,5-benzene tricarboxamide; Naphthalimide; Lanthanide; Sensing; Spectroscopy; Rheology; Fluorescent sensor; Self-assembly